Tip, torque and rotation of maxillary molars during distalization using Invisalign: a CBCT study - Dina Elfouly; Nadia M. El-Harouni; Hanan A. Ismail; Tarek El-Bialy; Ahmed Ghoneima (BMC, 2024)
Abstract Background Desirable molar distalization by bodily movement is challenging and can be difficult to achieve. This study investigated changes in molar angulation (mesiodistal tipping), molar inclination (buccolingual torque) and rotation during distalization using clear aligner therapy (CAT). Materials and methods This retrospective study included 38 cone beam computed tomographic images (CBCTs) taken for patients treated with molar distalization using CAT. The study evaluated pre- (T0) and post-treatment (T1) CBCTs of 19 adult patients (36.68 ± 13.50 years) who underwent maxillary molar distalization using Invisalign® aligners (Align Technology, Inc., San José, CA, USA) with a minimum of 2 mm distalization. Changes in maxillary molar tip, torque and rotation were measured for 61 molars (183 roots). Paired t-test was used to evaluate the differences between pre- and post-treatment readings. The level of significance was set at p ≤ 0.05. The reproducibility of measurements was assessed by the intraclass correlation coefficient (ICC). Results Molar angulation did not show significant change after distalization (p = 0.158) however, there was significant increase in buccal molar inclination (p = 0.034) and mesiobuccal molar rotation (p < 0.001). Conclusion Molar distalization of 2 mm did not cause significant molar tipping. Maxillary molars showed significant buccal inclination (increased torque) and mesiobuccal rotation after distalization.